Peran Orang Tua dalam Membentuk Rasa Percaya Diri Pada Anak Berkebutuhan Khusus di Tanjungpinang Timur - Dwi Silvani; Emmy Solina; Rahma Syafitri (CV Insan Kreasi Media, 2022)
This study discusses the role of parents in forming self-confidence in mentally retarded children. Children with mental retardation lack the confidence to go outside because of their limited communication. This study aims to determine how the role of parents in forming self-confidence in mentally retarded children. The researcher uses a qualitative method of research, with the technique of determining the informant, namely the Purposive Sampling technique. The researcher took as many as 11 informants who were considered able to answer and get the information needed by the researcher. With data collection techniques using observation, interviews and documentation. As well as in this study using the Structural Functional Theory from Robert K. Merton. Researchers used data analysis techniques for the Miles and Husberman model field, namely data reduction and data presentation. The results of this study and findings concluded that the discovery of forms of action and the role of parents in forming self-confidence in children can be done such as inviting and accompanying children to be in the play area with the aim of training children's courage and growing self-confidence, always giving praise for the work Children can make children happier and more enthusiastic, provide affection and show children to feel more valued and recognized, provide optimistic support and encouragement to children that parents believe and believe in the child. So here it can be shown that the role of parents for children, especially children with disabilities is very necessary.